Desert Locust Episode in Pakistan, 2018–2021, and the Current Status of Integrated Desert Locust Management. Issue 1 (5th January 2022) - Showler, Allan T; Shah, Sikandar; Sulaiman,; Khan, Sheharyar; Ullah, Sami; Degola, Francesca
Abstract: Desert locust, Schistocerca gregaria (Forskål) (Orthoptera: Acrididae), swarms during outbreaks, and plagues can invade many countries across vast regions of Africa and Asia, consuming substantial quantities of crops and rangeland vegetation. In the most recent desert locust episode, which originated in Saudi Arabia's remote interior in June 2018, and swarms entered Pakistan in March 2019, devastating important crops, such as cotton, Gossypium hirsutum L.; wheat, Triticum aestivum L.; and maize, Zea mays L., in >60 districts of Baluchistan, Punjab, Khyber Pakhtunkhwa, and Sindh provinces. A national emergency was declared on 1 February 2020. A national emergency was declared on 1 February 2020 and the Department of Plant Protection responded by conducting surveillance and control operations with the assistance of other Pakistani organizations, and multilateral and bilateral international aid agencies. Surveillance and control operations were performed by ground and by air, applying mostly oil-based ultra-low volume insecticide formulations combined with some nonconventional control tactics. The Pakistan government also established a detailed multi-phased locust control policy and a National Locust Control Center with rapid response units deployed to vulnerable districts. To prevent or mitigate desert locust-associated agricultural damage, additional improvements to surveillance and control approaches are needed. The desert locust's unique behaviors, and the magnitude and intermittency of swarming episodes, pose challenges to the development and implementation of coherent integrated pest management strategies. The status of a possible integrated approach to desert locust management, including proactive and preventive intervention strategies, is discussed.